2014
DOI: 10.4236/ajps.2014.54058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Bradyrhizobium japonicum</i> Inoculation and Supplementation with Phosphorus on Macronutrients Uptake in Cowpea (<i>Vigna unguiculata</i> (L.) Walp)

Abstract: The current study was conducted to assess the effects of phosphorus supplementation and Bradyrhizobium japonicum inoculation on the availability and uptake of N, P, K, Mg, Ca and Na on cowpea. The experiment was laid out in a split plot design where the main plots comprised two inoculation levels (with and without inoculation of B. japonicum) and sub plots contained four different levels of phosphorus (0, 20, 40, and 80 kg P/ha). The results indicated that B. japonicum inoculation and phosphorus supplementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…V1 = Cheupe, V2 = Selian 05, V3 = Selian 06. Bars followed by similar letter(s) are not significantly different.fixation, thus, providing adequate nitrogen which would have been supplied with nitrogenous fertilizer responsible for yield and yield components performance relative to control treatment.Despite the positive outcome observed, the literatures show that such related findings were also reported by[6] [21][22] [37]-[39]. Their report indicated significant increase in legume grain yield and the related yield…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…V1 = Cheupe, V2 = Selian 05, V3 = Selian 06. Bars followed by similar letter(s) are not significantly different.fixation, thus, providing adequate nitrogen which would have been supplied with nitrogenous fertilizer responsible for yield and yield components performance relative to control treatment.Despite the positive outcome observed, the literatures show that such related findings were also reported by[6] [21][22] [37]-[39]. Their report indicated significant increase in legume grain yield and the related yield…”
mentioning
confidence: 83%
“…Nyoki and Ndakidemi [21] [22] reported that Rhizobium inoculation significantly improved the yield and yield components of legumes such as number of pods per plant, number of seeds per pod, number of seeds per plant, 100-seed weight, and seed yield relative to control. The increase in seed yield could be due to high nodulation which results in high N 2 fixation and hence higher Dry Matter yield and Seed yield.…”
Section: Introductionmentioning
confidence: 99%
“…Leguminous plants such as Phaseolus vulgaris and Vigna unguiculata (Walp) have the capacity of forming symbiotic relationship with Rhizobium bacteria which transform atmospheric N 2 to soil nitrate or ammonium which can be utilized by leguminous plant for growth and development, in turn the leguminous plant provide housing and carbohydrates to the rhizobia [76]- [78]. Nyoki and Ndakidemi [79] disclosed that B. japonicum inoculants supplemented with phosphorus in cowpea improved the uptake of N, P, K, Mg, Ca and Na significantly relative to control. Makoi et al, [41] revealed that rhizobia inoculation significantly increased the uptake of P, K, Ca, and Mg in plant parts such as leaves, shoots, roots and pods of common beans (Phaseolus vulgaris L.).…”
Section: Rhizobium Inoculants Supplemented With Nutrient Elements P Amentioning
confidence: 99%
“…This consists of formation of nodules on host roots, which harbour the bacterial symbionts, and the N 2 fixation process in the nodules, which occurs thereafter [117]. In recent years, a number of Rhizobium inoculants have been developed and are primarily used for supplying nitrogen to plants by enhancing N 2 fixation [79]. Symbiotic nitrogen fixation in soybeans can provide from 65kg to more than 160 kg fixed nitrogen ha −1 [118] [119] representing about 40% -70% of soybeans nitrogen requirements.…”
Section: Rhizobium Inoculants Supplemented With Nutrient Elements K Amentioning
confidence: 99%
See 1 more Smart Citation